Analisis Kinerja Heat Exchanger Tipe Shell and Tube Berdasarkan Nilai Fouling Factor, Efesiensi, dan Pressure Drop sebagai Indikator Kinerja Operasional - Rantika Sekar Nandira; Sarah Dampang; Sesilia Romalinda; Sheryl Ayesha Bruning; Jatmiko (Jurnal Teknik Terapan, 2026)
The oil and gas industry heavily relies on the efficiency of shell-and-tube heat exchangers to maintain operational stability, optimize energy consumption, and preserve product quality. However, the performance of these units is often degraded by fouling, which increases thermal resistance. This study aims to evaluate the actual performance of a heat exchanger unit in the oil and gas industry by analyzing operational data over a specific period. The research methodology involved direct field observation and quantitative analysis based on key performance parameters, including the overall heat transfer coefficient, fouling factor, thermal efficiency, and pressure drop. The fouling factor was calculated as the difference between the clean and dirty heat transfer coefficients, while thermal efficiency was determined as the ratio of the actual heat transferred to the maximum possible heat transfer. Pressure drop analysis was conducted on both the shell and tube sides using friction factor correlations and fluid hydrodynamic parameters to evaluate flow characteristics. The results indicate a fouling factor of 0.2076 hr·ft²·°F/Btu, which significantly exceeds the standard threshold proposed by Kern (0.002–0.005 hr·ft²·°F/Btu). This high level of fouling results in a heat transfer efficiency of only 64.62%, well below the ideal operational standard of 75%. Hydrodynamic analysis shows that the pressure drop is very low (0.0003–0.0006 psi), indicating that the flow is in the laminar regime (Re < 2100). This laminar condition reduces heat transfer effectiveness due to the dominance of conduction and accelerates the deposition of solid particles on the heat transfer surface. Although the unit is still considered operable, the evaluation results highlight the need for immediate cleaning and flow rate optimization to restore the equipment’s performance to optimal levels and prevent further energy losses